2020
DOI: 10.1111/prd.12342
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis is an inflammatory disease of oxidative stress: We should treat it that way

Abstract: Periodontitis is a highly prevalent disease. As it progresses, it causes serious morbidity in the form of periodontal abscesses and tooth loss and, in the latter stages, pain. It is also now known that periodontitis is strongly associated with several nonoral diseases. Thus, patients with periodontitis are at greater risk for the development and/or exacerbation of diabetes, chronic obstructive pulmonary disease, and cardiovascular diseases, among other conditions. Although it is without question that specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
244
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(284 citation statements)
references
References 249 publications
(779 reference statements)
1
244
0
1
Order By: Relevance
“…Pro‐inflammatory responses are a self‐defense strategy against infection and injury. However, generation of ROS has been associated with elevated production of pro‐inflammatory cytokines, such as tumor necrosis factor‐α (TNF‐α), IL‐6, and IL‐1β, which are responsible for connective tissue destruction and bone resorption in the periodontium 36 . Previously, it has been reported that P .…”
Section: Discussionmentioning
confidence: 99%
“…Pro‐inflammatory responses are a self‐defense strategy against infection and injury. However, generation of ROS has been associated with elevated production of pro‐inflammatory cytokines, such as tumor necrosis factor‐α (TNF‐α), IL‐6, and IL‐1β, which are responsible for connective tissue destruction and bone resorption in the periodontium 36 . Previously, it has been reported that P .…”
Section: Discussionmentioning
confidence: 99%
“…In the subgingival microbiome, bacteria are exposed to many types of stress, including oxygen stress [ 44 ]. Oxygen stress is induced by oxygen and H 2 O 2 produced from microorganisms and neutrophils in the subgingival milieu [ 45 , 46 ]. Without enzyme neutralizing the H 2 O 2 , such as catalase, reactive oxygen species damage the bacterial DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no question that specific groups of oral bacteria that populate dental plaque play a causative role in the development of periodontitis, it is now thought that once the disease has been triggered, other factors play an equal, and possibly more important, role in the progression of periodontitis, particularly in severe periodontitis or in cases of periodontitis that prove difficult to treat. Once exposed to oral periodontal pathogenic bacteria, the host mounts a defense response mediated largely through the innate immune system . A critical cell type in the host response, polymorphonuclear neutrophils, can upregulate the production of pro‐inflammatory cytokines, matrix metalloproteinases, and reactive oxygen species, all of which contribute to increased oxidative stress and the tissue damage that occurs in periodontitis.…”
Section: Etiology Of Periodontal Diseasementioning
confidence: 99%
“…A critical cell type in the host response, polymorphonuclear neutrophils, can upregulate the production of pro‐inflammatory cytokines, matrix metalloproteinases, and reactive oxygen species, all of which contribute to increased oxidative stress and the tissue damage that occurs in periodontitis. An article in this volume of Periodontology 2000 discusses the characteristics of oxidative stress and its effects on the periodontium and examines approaches that attenuate the effects of reactive oxygen species, thereby potentially preventing the initiation of progression of periodontal disease . For example, resveratrol (3,5,4′‐trihydroxy‐ trans ‐stilbene), a natural phenol phytoalexin derived from a variety of plants in response to injury, may serve as an antioxidant to prevent disease.…”
Section: Etiology Of Periodontal Diseasementioning
confidence: 99%